Integrating Steam Elements into Primary Education: Experience and Effectiveness (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the implementation of STEAM (Science, Technology, Engineering, Art, Mathematics) elements in primary education and their role in improving the quality of teaching and learning. It emphasizes the importance of interdisciplinary integration, creative problem-solving, and the development of students’ critical and analytical thinking skills. The research highlights the need for teachers to apply innovative approaches, use digital resources, and create project-based learning environments that foster curiosity and collaboration among young learners.